2022
DOI: 10.3390/pr10081623
|View full text |Cite
|
Sign up to set email alerts
|

Application of Non-Dominated Sorting Genetic Algorithm (NSGA-II) to Increase the Efficiency of Bakery Production: A Case Study

Abstract: Minimizing the makespan is an important research topic in manufacturing engineering because it accounts for significant production expenses. In bakery manufacturing, ovens are high-energy-consuming machines that run throughout the production time. Finding an optimal combination of makespan and oven idle time in the decisive objective space can result in substantial financial savings. This paper investigates the hybrid no-wait flow shop problems from bakeries. Production scheduling problems from multiple bakery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Therefore, wherever possible, it is suggested to keep the processing route for a product separate from other products. Six bakery production datasets from Denmark were used by Babor et al 55 to increase the production efficiency. The results revealed that NSGA-II performed efficiently to reduce makespan by up to 12% and oven idle time by up to 61%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, wherever possible, it is suggested to keep the processing route for a product separate from other products. Six bakery production datasets from Denmark were used by Babor et al 55 to increase the production efficiency. The results revealed that NSGA-II performed efficiently to reduce makespan by up to 12% and oven idle time by up to 61%.…”
Section: Resultsmentioning
confidence: 99%
“…Figure15. An evaluation procedure of the NSGA-II55 . Non-dominated sorting divides the population into different ranks (F 0 , F 1 , F 2 , …).…”
mentioning
confidence: 99%
“…A few of the most well-known posteriori approaches have been based upon Evolutionary Algorithms (EA) [41], which includes NSGA-II [42] and Non-dominated Sorting Genetic Algorithm (NSGA) [43], [44], [45], MO Particle Swarm Optimization (MOPSO) [28], [46], and Pareto-frontier Differential Evolution (PDE) [47]. While the recently developed nature-inspired EAs have been utilized in real-life MOPs as well, the algorithms that have been mentioned above were first introduced more than ten years ago.…”
Section: Fig 3 Illustrates a Multimodal Moo Problemmentioning
confidence: 99%
“…In the process of solving, parameters such as the population size and the number of iterations of the algorithm need to be determined. Reasonable parameters will improve the accuracy and speed of the algorithm (44). In NSGA-II, the quality of the solution is affected by the algorithm parameters and reasonable value of parameters.…”
Section: Selection Of Parameters Of Algorithmmentioning
confidence: 99%